Research methods in intercultural communication : a practical guide - 4 0 16; 1970- Hua, Zhu; 5 (Malden, MA : Wiley-Blackwell, 2016)
The focus is on the process of interaction and what the participants achieve out of the experience in terms of new values, identities and practices--
Series; Title page; Copyright; Notes on Contributors; Acknowledgements; Preface; Part I Linking Themes, Paradigms, and Methods; 1 Identifying Research Paradigms; Introduction; What is a Paradigm?; What are the Significant Paradigms in Intercultural Communication studies?; Some General Questions about Paradigms; Key Terms; References; Further Reading and Resources; 2 Studying Culture; An Interpretive Constructivist Approach; Particular Social and Political Structures; Personal Trajectories; Underlying Universal Cultural Processes; Particular Cultural Products; Cultural Negotiation; Conclusion;Key TermsReferences; Further Reading and Resources; 3 Studying Identity; Introduction; Positivism, Essentialism and Strategic Essentialism: Ontology and Epistemology; Constructionism; From Identity Theories to Categorization Processes; Cultural, Ethnic, National, Identity/ies?; Conclusions; Key Terms; References; Further Reading and Resources; 4 Studying Discourse; Introduction; Intercultural Communication and Discourse Analysis: 1950s to 1980s; The Expanding Worlds of Discourse Studies: 1990s to 2010s; Four Models of Discourse; A Few Final Lessons about Studying Discourse; Acknowledgements;Key TermsReferences; Further Reading and Resources; Part II Key Issues and Challenges; 5 How to Identify Research Questions; Introduction; The Question of How: Nine Scenarios; Conclusion; Key Terms; References; Further Reading and Resources; 6 How to Research Multilingually: Possibilities and Complexities; Introduction; Insights on RM-ly; Developing Researcher Competence (vis-à-vis RM-ly Practice); Conclusion; Acknowledgements; Key Terms; References; Further Reading and Resources; 7 How to Research Interculturally and Ethically; Introduction; Cross-Cultural Approaches;An Intercultural ApproachThe Researcher as Cultural Outsider; The Researcher as Cultural Insider; From Insider/Outsider to Participant Observation; Researching in a Research Team that is Cross-/Intercultural in Nature; Ethical Considerations; Conclusion; Key Terms; References; Further Reading and Resources; 8 How to Assess Intercultural Competence; Assessment of Intercultural Competence -- Myths, Themes and Implications; Getting Started; Assessment of Intercultural Competence: Approaches/Methods/Tools; Assessment Issues; Assessment and Research; Acknowledgments; Key Terms; References;Further Reading and Resources9 How to Work with Research Participants: The Researcher's Role; Introduction; Critical Reflexivity and Process Interculturality; Co-constructing Research: Beyond Repressed Reflexivity?; An example; Conclusion; Key Terms; References; Further Reading and Resources; 10 How to Develop a Research Proposal; Getting Started; The Research Proposal; Ethics and Human Relations; Conclusion; Key Terms; References; Further Reading and Resources; Part III Methods; 11 Questionnaires and Surveys; What this Method is About; Why this Method and Why Not; How to Do It
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; Research.;Methodology. -- Intercultural communication;Intercultural communication -- 20; 20; Electronic books. -- 2